Insecticidal Activity and Chemical Composition of the Morinda lucida Essential Oil against Pulse Beetle Callosobruchus maculatus - Moses S. Owolabi; Eduardo Padilla-Camberos; Akintayo L. Ogundajo; Isiaka A. Ogunwande; Guido Flamini; Olaniyi K. Yusuff; Kirk Allen; Karen Isabel Flores-Fernandez; Jose Miguel Flores-Fernandez (The Scientific World Journal)
Insecticidal activity of essential oil extracted from Morinda lucida was tested on pulse beetle Callosobruchus maculatus, which is a pest that causes serious damage to several pulses. The insecticidal activity was compared with two pesticides, Phostoxin and Primo-ban-20. 120 mixed sex adult C. maculatus were introduced, along with 30 g of cowpeas. Four concentrations (0.40, 0.20, 0.10, and 0.05 μg/mL) of the M. lucida essential oil, Phostoxin, and Primo-ban-20 were tested. Essential oil chemical composition was analyzed by GC-MS. M. lucida essential oil showed a high toxicological effect, producing 100% mortality after 72 hours at a dose of 0.20 μg/mL. M. lucida essential oil had a potent insecticidal activity (LC90 = 0.629 μg/mL) compared to both pesticides, Phostoxin (LC90 = 0.652 μg/mL) and Primo-ban-20 (LC90 = 0.726 μg/mL), at 24 h. The main compounds of the essential oil were the oxygenated monoterpenoids, 1,8-cineole (43.4%), and α-terpinyl acetate (14.5%), and the monoterpene hydrocarbons, mostly sabinene (8.2%) and β-pinene (4.0%). Results clearly indicate that M. lucida essential oil can be used as an effective alternative for pulse beetle C. maculatus control, and it could be tested against other pulse beetles affecting Asia and Africa and throughout the world, thereby reducing use of synthetic pesticides.